SPECT-CT Imaging of Dog Spontaneous Diffuse Large B-Cell Lymphoma Targeting CD22 for the Implementation of a Relevant Preclinical Model for Human - Etienne, Floriane; Berthaud, Maxime; Nguyen, Frédérique; Bernardeau, Karine; Maurel, Catherine; Bodet-Milin, Caroline; Diab, Maya; Abadie, Jérôme; Gouilleux-Gruart, Valérie; Vidal, Aurélien; Bourgeois, Mickaël; Chouin, Nicolas; et al. (Frontiers in Oncology, 2020)
Antibodies directed against CD22 have been used in radioimmunotherapy (RIT) clinical trials to treat patients with diffuse large B-cell lymphoma (DLBCL) with promising results. However, relevant preclinical models are needed to facilitate the evaluation and optimization of new protocols. Spontaneous DLBCL in dogs is a tumor model that may help accelerate the development of new methodologies and therapeutic strategies for RIT targeting CD22. Seven murine monoclonal antibodies specific for canine CD22 were produced by the hybridoma method and characterized. The antibodies’ affinity and epitopic maps, their internalization capability and usefulness for diagnosis in immunohistochemistry were determined. Biodistribution and PET imaging on a mouse xenogeneic model of dog DLBCL was used to choose the most promising antibody for our purposes. PET-CT results confirmed biodistribution study observations and allowed tumor localization. The selected antibody, 10C6, was successfully used on a dog with spontaneous DLBCL for SPECT-CT imaging in the context of disease staging, validating its efficacy for diagnosis and RIT. This first attempt at phenotypic imaging on dogs paves the way to implementing quantitative imaging methodologies that would be transposable to humans in a theranostic approach. Taking into account the feedback of existing human radioimmunotherapy clinical trials targeting CD22, animal trials are planned to investigate protocol improvements that are difficult to consider in humans due to ethical concerns.